A Gluten‐Free Biscuit Fortified with Lemon IntegroPectin. Issue 5 (1st February 2022) - Nuzzo, Domenico; Scurria, Antonino; Picone, Pasquale; Guiducci, Alessandro; Pagliaro, Mario; Pantaleo, Giuseppe; Albanese, Lorenzo; Meneguzzo, Francesco; Ciriminna, Rosaria
Abstract: We report the first outcomes of producing a gluten‐free biscuit by replacing 2.5 wt% of the rice flour used in the preparation of a commercial gluten‐free cookie with lemon IntegroPectin, a new citrus pectin obtained from lemon processing waste via hydrodynamic cavitation. The cookie's friability, palate adhesion, flavor persistency and compactness remain virtually unchanged, whereas sapidity and color improve. Only the sweetness and the smell (flavor) of the functionalized cookie are lower than those of the commercial biscuit. The enhanced heat resistance and unique structure of this new citrus pectin unveiled by XRD and TGA structural and thermal analyses make it suitable for the straightforward functionalization of bakery products with numerous potential health benefits. Abstract : The enhanced heat resistance and unique structure of lemon IntegroPectin, a new citrus pectin obtained from lemon processing waste via hydrodynamic cavitation, make it suitable for the straightforward functionalization of bakery products with numerous potential health benefits, shown in this case with a commercial gluten‐free cookie.